QUALITY COSTS CONCEPT AND MEASUREMENT – DOES A REAFFIRMATION IN A NEW DIRECTION NEEDED? - Velkoska, Cvetanka; Tomov, Mite (International Scientific Journal Vision, 2021)
This study primarily aims at presenting a realistic picture of the utilitarian nature of quality costs in companies around the world. This has led to researching the quality costs applications levels, the percentage share of the total quality costs, the percentage share measuring the quality costs categories, as well as the measured percentage shares of the quality costs in the companies. The analytical research methodology relies on an integrated chronological, comparative, logical and systematic analysis of scientific literature, complemented by inductive and deductive methods. The research results confirm the need to raise the awareness for, determination, and commitment to a broader application of the quality costs concept through an understanding and integration of the new societal values of contemporary operations, whereby the understanding of the application of the quality costs concept will deepen and the quality costs concept itself will shift from the margins of a purely theoretical concept. We expect that the contemporary ambitious concepts such as Sustainability, Industry 4.0, Quality 4.0, Business Process Reengineering, Circular economy – Remanufacturing, Innovation 5.0 will contribute to the development a higher level of quality maturity which, in turn, will make the application of quality costs more attractive. In particular, as this will reflect on the redesigning and redefining the quality costs’ structure to include new modernized elements of quality costs, and the quality costs concept will be reaffirmed in a new direction and will become recursive.